Endogenous technologies and productivity in rice production: Roles of social instability in Myanmar since 2021 - Takeshima, Hiroyuki; Aung, Zin Wai; Masias, Ian; Minten, Bart (Wiley, 2024)
Despite technologies' critical roles in agricultural productivity, evidence is scarce on how conflict affects technology adoption and consequent agricultural productivity, often due to a lack of data in fragile states. Our study contributes to filling this knowledge gap by using unique large-scale data on rice producers before and after a military coup in Myanmar in 2021 that led to a significant increase in conflicts in the country. We find that the increase in violent events including those in adjacent townships significantly changed the rice production function in both factor-neutral and non-neutral ways. Specifically, increased violent events have been generally associated with downward factor-neutral shift in production function, and more importantly, increased output elasticity to agricultural capital (equipment) owned (in other words, reduced output resilience against capital ownership shocks). Our evidence also suggests that this has been led partly through reduced access to agricultural extension services, which would otherwise help farmers maintain productivity even with limited capital ownership by substituting it with human capital and skills. Our results consistently hold for both panel and cross-sectional production functions across various specifications and particularly in Lower Myanmar. Results also indicate that lower mechanization service fees partly mitigate these effects.